Analisis Strategi Pemasaran Digital pada Batik Equatik - Jannah, Kuntum Khoiru Nisa Miftah Ul; Purnomo, Didit (Universitas Muhammadiyah Surakarta, 2025)
Batik Equatik is a fashion product that combines culture and current trends. A product needs to have a good marketing strategy, nowadays online sales are rampant in Indonesia because the new era of digital marketing has entered the practice of modern society. Now Social Media plays a big role in promoting a product including in the fashion world, therefore Equatik batik needs to have the right strategy to be able to enter the digital market in Indonesia. The purpose of this study is to analyze what marketing strategies Equatik batik should have as a new product. Through SWOT analysis with the IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation) matrices, both explain how the factors of strengths, weaknesses, opportunities and threats that exist in digital marketing in Equatik batik. The results of the analysis show that the SO strategy has the highest value, namely by intensifying promotions on social media so that products are increasingly recognized, providing stable and loyal prices to customers, providing safe and affordable shipping services and building clear market segmentation in order to expand reach to the public.